2017
DOI: 10.1038/s41598-017-16826-z
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient (ADC) predicts therapy response in pancreatic ductal adenocarcinoma

Abstract: Recent advances in molecular subtyping of Pancreatic Ductal Adenocarcinoma (PDAC) support individualization of therapeutic strategies in this most aggressive disease. With the emergence of various novel therapeutic strategies and neoadjuvant approaches in this quickly deteriorating disease, robust approaches for fast evaluation of therapy response are urgently needed. To this aim, we designed a preclinical imaging-guided therapy trial where genetically engineered mice harboring endogenous aggressive PDAC were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…Post mortem analyses of terminal stage PDAC specimens have shown higher tumor cellularity compared to resectable PDAC specimens, which likely represent earlier tumor development stages (14). In line with this observation we previously demonstrated that higher regional tumor cellularity identified in PDAC resection specimens was associated with a significantly worse overall survival and that the pre-operative DW-MRI-derived ADC parameter could serve as a non-invasive marker thereof (15,16). Upholding these findings, the current analysis identified (12).…”
Section: Discussionsupporting
confidence: 84%
“…Post mortem analyses of terminal stage PDAC specimens have shown higher tumor cellularity compared to resectable PDAC specimens, which likely represent earlier tumor development stages (14). In line with this observation we previously demonstrated that higher regional tumor cellularity identified in PDAC resection specimens was associated with a significantly worse overall survival and that the pre-operative DW-MRI-derived ADC parameter could serve as a non-invasive marker thereof (15,16). Upholding these findings, the current analysis identified (12).…”
Section: Discussionsupporting
confidence: 84%
“…Slug-YFP mice were generously provided by Robert A. Weinberg, Whitehead Institute for Biomedical Research, Cambridge, MA. For the in vivo treatment, animals received refametinib (BAY86-9766) as published previously [15]. Primary tumors were minced and digested with collagenase (STEMCELL Technologies, 07902).…”
Section: Methodsmentioning
confidence: 99%
“…Ptf1a wt/cre ; Kras wt/LSL-KrasG12D ; Tp53 fl/fl (CKP) mice developing spontaneous aggressive PDAC were generated as previously described 42 and treated for 48 h with the MEK inhibitor refametinib 43 . Patient-derived xenografts were generated by subcutaneous transplantation of resected PDAC tumors or from purified circulating tumorigenic cancer stem cells in NOD/SCID/IL2y-mice and propagated in NMRI:nu/nu mice after engraftment 23 .…”
Section: Mice and Treatmentsmentioning
confidence: 99%